2013
DOI: 10.1007/s10151-013-1095-7
|View full text |Cite
|
Sign up to set email alerts
|

Transanal minimally invasive surgery for total mesorectal excision (TAMIS–TME): results and experience with the first 20 patients undergoing curative-intent rectal cancer surgery at a single institution

Abstract: Transanal TME is a feasible method for oncologic resection of locally advanced mid- and distal-rectal cancer with curative intent. It has special application for patients with obesity and anatomic constraints such as a narrow male pelvis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
144
0
10

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 189 publications
(166 citation statements)
references
References 39 publications
(46 reference statements)
9
144
0
10
Order By: Relevance
“…As in the present series, other reports4, 5, 6, 7, 8, 9, 10, 11 24, 25 have described the absence of intra‐abdominal infection.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…As in the present series, other reports4, 5, 6, 7, 8, 9, 10, 11 24, 25 have described the absence of intra‐abdominal infection.…”
Section: Discussionsupporting
confidence: 83%
“…Among studies of colorectal cancer treated with hybrid NOTES, no local recurrence has been reported at 6 months6 24, 25 or 9 months11. There was a single local recurrence in one series31 with a median follow‐up of 29 months.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Several potential advantages have been postulated. Atallah was the first to describe this combination of techniques including a detailed video and the results of the 20 first cases [8,9] . Rectal distention with CO 2 combined with magnified optics permits excellent visualization of tissue planes.…”
Section: Introduction and Historymentioning
confidence: 99%